Fiqh Siyasah; Konsep, Sejarah, dan Dinamika Perkembangannya - Ahwadzy, Muhammad Arfan; Ahwadzy, M. Arfan (Siyasah, 2025)
Fiqh siyasah is an essential part of Islamic intellectual heritage, playing a strategic role in responding to the dynamics of power and state governance throughout Islamic civilization history. This article aims to examine the fundamental concepts, history, and developmental dynamics of fiqh siyasah from the classical period to the contemporary era. This study employs a qualitative approach using library research methods, with data obtained from relevant primary and secondary literature, which are then analyzed descriptively, historically, and normatively. The findings indicate that fiqh siyasah possesses a dynamic and adaptive character, enabling Islamic political principles to remain relevant in addressing contemporary challenges. Socio-political changes in various Muslim countries demonstrate that fiqh siyasah can be contextualized within modern governmental systems without losing its sharia values. This article concludes that fiqh siyasah functions not only as an intellectual legacy but also as a normative and ethical foundation for building just governance. These findings provide practical contributions in formulating models of the relationship between religion and state that are inclusive, contextual, and aligned with the principles of substantive democracy.